FoxP3+CXCR5+CD4+ T cell frequencies are increased in peripheral blood of patients with primary Sjögren's syndrome. (10th January 2019) - Ivanchenko, M; Aqrawi, L A; Björk, A; Wahren-Herlenius, M; Chemin, K
Abstract: We recently explored the expression of CXCR5 on T and B cells from peripheral blood of patients with primary Sjögren's syndrome (SS). Here we investigated the frequency of CD25 + FoxP3 + CD4 + regulatory T cells (Tregs ) among CXCR5 + CD4 + follicular cells in the same cohort of patients. We confirm that the frequency of Tregs among follicular T cells is increased in SS patients and also provide novel data showing an increased frequency of PD-1 expressing cells among CXCR5 + FoxP3 + CD4 + T cells. Graphical Abstract: